Korean patients with hereditary cancer: a prospective multicentre cohort study protocol exploring psychosocial and health outcomes - Boyoung Park; Sun-young Kong; Dongju Won; Jong Eun Park; Jun-Kyu Kim; Mi-Ae Jang; Jung-Sook Ha; Kyoung-Bo Kim (BMJ Open)
Introduction Although genetic testing for hereditary cancers is increasing, data on health attitudes based on genetic pathogenicity are limited. This cohort study aims to establish three subcohorts based on genetic testing results to assess the health impact of genetic variations. This study evaluates changes in participant quality of life (QoL), unmet needs and mental health over time based on their genetic variant status.Methods and analysis This prospective cohort study will recruit 1435 patients with suspected hereditary cancer who have undergone BRCA1/2 or next-generation sequencing (NGS) testing. The study began in July 2023 and will continue until December 2027. By 2026, participants will be surveyed up to four times annually during their outpatient visits. The survey consists of 342 items across 5 domains: comorbidities (96), health behaviours (80), QoL (41), unmet needs (75) and mental health (50). Data were collected using 11 validated surveys. In addition, information on the chronic diseases, cancer diagnoses, medical history and treatment history of participants will be extracted from their electronic medical records to analyse their health status and cancer treatment experiences. Genetic variant data from BRCA1/2 and NGS will be used to classify participants into three subcohorts: pathogenic variants, variants of uncertain significance and undetectable mutations. A three-generation pedigree that includes details such as the year of cancer diagnosis, age at diagnosis, cancer type, survival status of family members and age at death will be constructed for each participant. The collected data will be linked to secondary sources such as cancer registries and National Health Insurance Service data to provide a comprehensive analysis of the impact of hereditary cancer on health and survival.Ethics and dissemination The study protocol was approved by all the Ethics Committees: the National Cancer Center IRB (NCC2023-0179), the Samsung Medical Center IRB (SMC2023-09-057), the Yonsei University Health System, Severance Hospital IRB (4-2023-0627), the Hanyang University Guri Hospital IRB (GURI2023-08-021) and the Keimyung University IRB (DSMC IRB 2024-05-048). The study outcomes will be disseminated through conference presentations, peer-reviewed publications and social media.Trial registration number KCT0009460.